Internet of Things on the Air Quality Monitoring System Using a Web Server - Sumardi Sadi; Sri Mulyati; Perdana Bagaskara Setiawan (Asian Journal of Healthcare Analytics, 2022)
The increase in the amount of air pollution that causes global warming and the lack of attention to harmful gases, such as CO, PM 2.5, and NO2 can have a negative impact, on health and can even cause death, if it is ignored by people who breathe it. One of the popular information media today is the web, a tool that can monitor air quality levels and by utilizing advances in technology this monitoring system can be monitored via a Web Server. In this study, using an AVR microcontroller type ATmega 328p as a central control unit, and an ESP 8266-01 as a controller that handles communication between the microcontroller and the internet network. In addition, this system uses the C language as a configuration between the microcontroller and the ethernet system. The level of air pollution is measured by the MQ 07 sensor which functions to measure CO levels, MQ 135 to measure NO2 levels, and the Dust Sensor to measure PM 2.5. Test results Obtain PPM (parts per million) values ​​for CO levels of 0.25 ppm, NO2 of 0.83 ppm, PM 2.5 of 0.10 g/m3 and the temperature can be seen directly through the dashboard thingboard.